The Twin Legacies of a Scholar-Teacher: The Publications and Dissertation Advisees of Allen Forte - David Carson Berry (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2009)
This article tabulates the publications and dissertation advisees of the music theorist Allen Forte; they are called the “twin legacies” of one whose work in academe has been devoted to both scholarship and teaching. The publications, issued between 1955 and early 2009, are divided into nine categories, each ordered chronologically: (1) Books; (2) Articles; (3) Addresses, Responses, Forums, and Discussions; (4) Introductions, Forewords, Editorials, and Memorials; (5) Encyclopedia and Dictionary Entries; (6) Reviews; (7) Letters to Editors; (8) Libretto Translations, Liner Notes, and Recordings; and (9) Editorial Work. Entries are annotated with one or more of the following subfields, as necessary: Remarks, Ancillaries, Later Editions, Reprints, Translations, and (for books) Reviews. Excluding items only edited by Forte, these publications consist of ten books, sixty-three articles, and thirty-six other types of publications. An Appendix presents an abbreviated chronological listing of all his publications, without regard to categories. The list of advisees consists of the name, dissertation title, and date of submission for each of Forte’s seventy-two Ph.D. advisees at Yale University. The list is ordered chronologically by dissertation submission (which ranges from 1968 to 2002), and each advisee is given an “FA” number to denote his or her ordering among the advisees. (“FA” stands for “Forte Advisee,” and is also a retrograde of Allen Forte’s initials.) Together, the two tabulations document some of the reasons that Forte’s legacy looms so large in music theory. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part I).